1997
DOI: 10.1159/000201483
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Hypokinesia in Crohn’s Disease

Abstract: For the purpose of shedding some light upon the possible mechanisms involved in gallstone formation in patients with Crohn’s disease, we have investigated gallbladder emptying by means of ultrasonography in two groups of subjects: controls (n = 40) and Crohn’s disease (n = 30). Diminished gallbladder emptying after a liquid fatty-meal stimulus was observed in patients with Crohn’s disease when compared with controls (p < 0.001). Also, the values for the residual gallbladder volume (RGV) and maximal decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The authors speculate that in these patients, decreased bile acid absorption would result in higher bilirubin solubilisation in the colon and increased bilirubin reabsorption. iii) Additional mechanisms for gallstones in IBD patients include prolonged fasting state, parenteral nutrition and decreased gall bladder motility [27, 28]. One study concluded that intestinal surgery itself, not the altered anatomy after surgery would increase the risk of gallstones [4].…”
Section: Discussionmentioning
confidence: 99%
“…The authors speculate that in these patients, decreased bile acid absorption would result in higher bilirubin solubilisation in the colon and increased bilirubin reabsorption. iii) Additional mechanisms for gallstones in IBD patients include prolonged fasting state, parenteral nutrition and decreased gall bladder motility [27, 28]. One study concluded that intestinal surgery itself, not the altered anatomy after surgery would increase the risk of gallstones [4].…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism has been accepted for a long time as the most important in CD-related gallstone formation 27 ; however, recent animal and human data have shown that cholesterol supersaturation is a transient phenomenon after ileal resection and an increased channeling of cholesterol into de novo synthesis to compensate for increased intestinal loss of bile acids rapidly occur 28 ; (2) a reduced gallbladder motility in patients with CD, which may facilitate GD formation in the presence of cholesterol supersaturation. In this regard, some evidence has been seen of an impaired fatty-meal-induced gallbladder motility in patients with ileal and ileocolonic disease, 29,30 and Annese and Vantrappen also demonstrated decreased gallbladder contractility in patients with inactive CD 31 ; (3) a marked reduction in gallbladder emptying associated with fasting and total parenteral nutrition; a prolonged fasting state or the use of total parenteral nutrition both can induce biliary sludge due to reduced gallbladder emptying. 32 Because these factors are common in patients undergoing surgery for CD, the association between stones and intestinal resection may be attributed also to these perioperative defects in gallbladder motility.…”
Section: Discussionmentioning
confidence: 99%
“…After ileal resection, anaerobic bacteria colonization can also deconjugate bile acids decreasing the absorptive capacity of mucosa. Furthermore, CD patients have reduced gallbladder motility owing to prolonged fasting period, which may also lead to the development of cholelithiasis . Systematic cholecystectomy after an ileal resection is, however, not recommended …”
Section: Other Hepatic Manifestations Than Psc Affecting Ibd Patientsmentioning
confidence: 99%